RANCANG BANGUN PENGENDALIAN KECEPATAN MOTOR INDUKSI TIGA FASA BERBASIS PLC SCADA DENGAN HMI HAIWELL MELALUI SISTEM JARAK JAUH - Damayanti, Eva; Leanardi, Alji (Jurnal TEDC; Vol 20 No 1 (2026): JURNAL TEDCDO - 10.70428/tedc.v20i1.1438, 2026)
Three-phase induction motors are vital components in industry, but controlling their speed requires special methods and remote monitoring for greater efficiency. This research aims to design a motor speed and rotation direction control system integrated with PLC, SCADA, and Haiwell HMI. The research methods include literature study, system design, hardware assembly, programming, and data testing. This system uses Delta 007EL021 VFD as a frequency regulator to control speed and rotation direction. The VFD is controlled by an Omron CP2E ND20DR-A PLC through a CP1W-CIF11 communication module. For the monitoring interface, a Haiwell B7s HMI connected to Haiwell Cloud SCADA is used, enabling operation via a smartphone as long as there is an internet connection. The test results show that the system works well in real-time. The motor speed is proven to be linearly affected by frequency; at a frequency of 5 Hz, the motor rotates at 148 rpm, and at 50 Hz, it reaches 1496 rpm. This integration has succeeded in facilitating remote monitoring and simplifying conventional complex wiring.